Rola partii politycznych w redefiniowaniu stosunku przedstawicielskiego - Szymanek, Jarosław (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: The role of political parties in redefinition of the ratio of representative The main theme of this article is the role of political parties in the system of representation of interests that are expressed at the national forum of political representation, which is the parliament. The said system originated without political parties, which were to emerge and show their political weightiness later on, to nowadays become an indispensable element of the political process. The latter involves both election and ruling, but also voicing of the interests, opinions, demands, and expectations of the electorate. Parties, mostly viewed critically today, at the dawn of the representative system were perceived radically different, that is, as a remedy to the aches of the said system, capable of eradicating the corruption. They were also compounded with the free (representative) mandate, which was to be another antidote to corruption as well as other pathological phenomena. It was believed that the formula where a deputy represents the general interests of the electorate is the most consistent with the form of political party. Therefore parties were designed as clearly additional and auxiliary element. Slowly but surely, however, they gained autonomy, attaining their separate and independent significance to the degree where they, as it is claimed contemporarily, reshaped the formula of the mandate, turning it form individual to collective, with political parties themselves as its owners that have become the primary subjects and agents; first of all, of the political competition, then, of the parliamentary political games. All in all, political parties seen through a prism of representation, are a kind of pendentive thereof. Key words: political party, representation, deputy, election, parliament, representative mandate